2016
DOI: 10.1111/japp.12172
|View full text |Cite
|
Sign up to set email alerts
|

Epistemic Injustice and Illness

Abstract: This article analyses the phenomenon of epistemic injustice within contemporary healthcare. We begin by detailing the persistent complaints patients make about their testimonial frustration and hermeneutical marginalization, and the negative impact this has on their care. We offer an epistemic analysis of this problem using Miranda Fricker's account of epistemic injustice. We detail two types of epistemic injustice, testimonial and hermeneutical, and identify the negative stereotypes and structural features of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
137
0
24

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 206 publications
(162 citation statements)
references
References 28 publications
1
137
0
24
Order By: Relevance
“…A growing body of work has suggested that individuals suffering from ill health are more vulnerable to testimonial injustice, and this vulnerability exists across the different stages and epistemic practices of medical work 10 11 30–32. There is a risk of testimonial injustice when, for example, the inadvertent negative stereotyping of an illness or disability (on the part of a healthcare professional) constrains the patient's epistemic contribution to consultations, and wider conversations, about their condition.…”
Section: Epistemic Injusticementioning
confidence: 99%
See 2 more Smart Citations
“…A growing body of work has suggested that individuals suffering from ill health are more vulnerable to testimonial injustice, and this vulnerability exists across the different stages and epistemic practices of medical work 10 11 30–32. There is a risk of testimonial injustice when, for example, the inadvertent negative stereotyping of an illness or disability (on the part of a healthcare professional) constrains the patient's epistemic contribution to consultations, and wider conversations, about their condition.…”
Section: Epistemic Injusticementioning
confidence: 99%
“…Fricker classifies these wrongs and harms as ‘epistemic injustice’. Developing its application, Havi Carel and Ian Kidd have recently argued that Fricker's framework provides a fruitful perspective for analysing the distinctive epistemic injustice that may arise within the healthcare arena, and in particular in healthcare consultations, medical education and policymaking 10 11. This paper applies this theoretical framework to the case of CFS/ME and examines the ethical repercussions of the deep differences between lay and healthcare professional perspectives on this illness.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anywhere in organizations and societies where there are gendered, ethnic, disabled, or other minorities, there is a likelihood of many epistemic injustices of both forms occurring ). An employee with a healthcare or disability issue may either not be believed by epistemically unjust managers or doctors (testimonial), or find it difficult to explain, formulate, and secure reasonable adjustments (hermeneutic) (Kidd and Carel 2017). Women may report having their workplace testimonials or contributions ignored or 'mansplained' back to them in an epistemically unjust culture, where men are unfairly discrediting, then re-appropriating, their role as a credible knower (Luzzi 2016).…”
Section: Epistemic Injusticementioning
confidence: 99%
“…Surprising given the general links between epistemological concerns, such as how we acquire knowledge, and ethical concerns, such as how we deliver fair hearings or deliberate on policy-making (e.g., Griffin 2011;Kidd et al 2017). Significant because a failure to consider these epistemic-ethical relationships risks leaving the spread of ignorance and confusion inadequately theorized (Oreskes and Conway 2012), and fails to hold accountable those who disregard 'epistemic goods' such as 'truth,' 'justification,' 'wisdom,' and 'understanding' as responsible for the consequences of their attitudes and actions (Matheson and Vitz 2014).…”
Section: Introductionmentioning
confidence: 99%